Solar Bubble Dryer - a novel and low-cost drying technology commercialized and marketed globally - CGIAR Research Program on Rice (2019)
The Solar Bubble Dryer (SBD) is a low-cost drying technology developed by IRRI, Hohenheim University and GrainPro. It is designed to improve village level drying by farmers and farmers groups.The SBD is mobile and is completely independent from fuel or the power grid, and therefore has very low operating cost. Current models have 0.5 ton and 1 ton batch capacity. The first version of the SBD was commercialised in September 2014 and currently,508 units are sold by GrainPro world wide.